Social support and subjective well-being among postgraduate medical students: the mediating role of anxiety and the moderating role of alcohol and tobacco use. Issue 12 (December 2021) - Huang, Zewen; Zhang, Lejun; Wang, Junyu; Xu, Lu; Liu, Zhuang; Wang, Tingting; Guo, Ming; Xu, Xi; Lu, Heli
Abstract: Medical students often face pressures from various sources in the course of postgraduate studies, and these factors have a negative impact on their subjective well-being. Previous researches have revealed that social support is a vital factor influencing subjective well-being, but unfortunately the underlying mechanism for this is unclear, especially for postgraduate medical students. The current study has inspected the effects of social support on subjective well-being of postgraduate medical students, the mediating role of anxiety and the moderating role of alcohol and tobacco use in the association between social support and subjective well-being of postgraduate medical students. A sample of 900 postgraduate medical students (Mage = 27.01 years, SD = 3.33) from The Second Affiliated Hospital of Nanchang University completed the Social Support Rating Scale, the Generalized Anxiety Disorder-7, the Tobacco and Alcohol Use Questionnaire and the Subjective Well-Being Scale. Analysis of the structural equation model revealed that anxiety partially mediated the relationship between social support and subjective well-being of postgraduate medical students, while alcohol and tobacco use moderated the relationship between anxiety and subjective well-being of postgraduate medical students. This study revealed how social support act upon subjective well-being of postgraduate medical students. This study provides a theoretical basis for promoting and enhancing the subjective well-being of postgraduate medical students. Abstract : Medical students; Subjective well-being; Social support; Anxiety; Alcohol and tobacco use.